Cytidine nucleoside analog is an effective antiviral drug against Trichomonasvirus - Narayanasamy, Ravi Kumar; Rada, Petr; Zdrha, Alois; van Ranst, Marc; Neyts, Johan; Tachezy, Jan (Journal of microbiology, immunology, and infection, 2022)
BACKGROUND: Trichomonas vaginalis is the causative agent of a sexually transmitted disease in humans. The virulence of the parasite depends on multiple factors, including the presence of endosymbiotic dsRNA viruses. The presence of Trichomonasviruses (TVV) was associated with more severe genital symptoms, increased proinflammatory host reactions, and modulated parasite sensitivity to metronidazole. However, no efficient antiviral drugs are available against TVV to derive isogenic TVV-positive and TVV-negative cell lines that are essential for investigations of the TVV impact on T. vaginalis biology. METHODS: 7-Deaza-2'-C-methyladenosine (7d2CMA) and 2'-C-methylcytidine (2CMC) were used for TVV inhibitory assay. TVV replication was monitored using quantitative reverse transcription PCR (RT qPCR) and western blotting. Modeling of TVV1 RNA-dependent RNA polymerase (RdRp) was performed to visualize the inhibitor-RdRp interaction. Susceptibility to metronidazole was performed under aerobic and anaerobic conditions. RESULTS: We demonstrated that 2CMC but not 7d2CMA is a potent inhibitor of TVV replication. Molecular modeling suggested that the RdRp active site can accommodate 2CMC in the active triphosphate nucleotide form. The effect of 2CMC was shown on strains infected with a single and multiple TVV species. The optimal 2CMC concentration (10 μM) demonstrated strong selectivity for TVVs over trichomonad growth. The presence of TVV has no effect on T. vaginalis metronidazole susceptibility in derived isogenic cell lines. CONCLUSIONS: 2CMC acts against TVVs and represents a new inhibitor against Totiviridae viruses. Our isogenic clones are now available for further studies of various aspects of T. vaginalis biology related to TVV infection.
Keywords: Cytidine; RNA-dependentní RNA-polymerasa; Nucleosides; antivirové látky; nukleosidy; paraziti; Metronidazole; Trichomonas vaginalis; cytidin; RNA Viruses; Animals; Antiviral Agents; lidé; RNA-Dependent RNA Polymerase; metronidazol; Humans; zvířata; RNA-viry; Parasites; Totiviridae